Application of Novel Recovery Techniques to Enhance the Resilience of Transportation Networks. Issue 1 (December 2018) - Zhang, Ning; Alipour, Alice; Coronel, Laura
Resilience is an important characteristic of the transportation system. It reflects the network's ability to mitigate shocks, provide alternatives, and rapidly recover to a target performance level. Earthquakes can cause the transportation network to experience severe disruptions that significantly reduce network resilience. To prevent long-term closures after earthquakes, the development of innovative approaches for their rapid restoration is necessary. This paper uses the recent developments in accelerated bridge construction (ABC) techniques as a means to enhance the rapid recovery of the system. ABC techniques often come with increased initial construction costs. In most cases, the additional cost is offset by the improvement of the network performance. To examine the efficiency of ABC techniques on the rapid recovery and on the network performance after earthquakes, the direct and indirect costs during the entire recovery period were analyzed and the relationship between network recovery time and network performance was estimated under different construction techniques. Additionally, the effect of using the incentive method to reduce the repair time was studied. The results show that the use of ABC techniques and the incentive method have great potential to minimize the transportation network's indirect losses, improve network performance, increase the network's resilience by decreasing recovery time, and justify the additional initial costs associated with these techniques.